Peningkatan kompetensi pedagogik guru RA melalui pelatihan modul ajar berbasis Kurikulum Merdeka di Kecamatan Pabelan, Kabupaten Semarang - Latifah, Ibdaul; Marwiyati, Sri; Setiyarini, Budi; Azizah, Azza Nur; Rohmah, Taufiku (Penamas: Journal of Community Service, 2025)
This community service program (PkM) aimed to provide mentoring for teachers across Pabelan Subdistrict in developing differentiated lesson modules to support the implementation of the Merdeka Curriculum. The program was delivered through training sessions that included lectures, discussions, hands-on practice, and guided support in module development. Participants included 53 RA (Islamic early childhood education) teachers from 14 early childhood education institutions in Pabelan Subdistrict. The program adopted a Participatory Action Research (PAR) approach, beginning with a needs assessment of the target group and then proceeding to participatory implementation with the teachers. Throughout the mentoring process, teachers were given greater opportunities and autonomy to apply their expertise in designing differentiated modules aligned with the Merdeka Curriculum. The results indicated an improvement in teachers' pedagogical competence, reflected in a stronger understanding of the Merdeka Curriculum, particularly in child-centered lesson planning, formulating learning objectives aligned with RA learning outcomes, and designing contextual, flexible modules that respond to students' needs.